PENGEMBANGAN MEDIA PEMBELAJARAN MODUL DIGITAL INTERAKTIF PADA MATA PELAJARAN FIQIH MATERI, ZAKAT, INFAQ, DAN SEDEKAH SISWA KELAS X DI MA MUSLIMAT NU PALANGKA RAYA - Aida Nurul Hikmah; Meliny Meliny; Abdul Azis (ADIBA : JOURNAL OF EDUCATION, 2024)
This study aims to develop interactive digital module-based learning media on Fiqh subjects on zakat, infaq, and sedekah for class X students of MA Muslimat NU Palangka Raya. Using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, this study produces learning media that has been validated by material and media experts. The validation results show a significant level of feasibility, with a score of 78% from material experts ("Feasible" category) and 74% from media experts ("Feasible" category). The assessment from educators reached 96% ("Very Feasible" category). Implementation in the classroom showed a positive response from students, who reported that this learning media was interesting, easy to understand, and not boring. The interactive digital module developed integrates various multimedia elements such as text, images, audio, short lecture videos, and interactive quiz features (Quiziz), allowing flexible learning access both online and offline. The development of this media provides a solution to the problems of monotonous learning and the lack of media variation in the classroom, while also providing innovative teaching aids for teachers in delivering zakat, infaq, and sedekah materials.